До 90-річчя кафедри "Передача електричної енергії" Національного технічного університету "Харківський політехнічний інститут" - Барбашов, Ігор Володимирович; Бондаренко, Володимир Омелянович; Ніжевський, Віктор Ілліч; Шевченко, Сергій Юрійович (Національний технічний університет "Харківський політехнічний інститут", 2020)
Статтю присвячено 90-річчю кафедри "Передача електричної енергії" Національного технічного університету "Харківський політехнічний інститут". Представлено основні етапи створення та розвитку кафедри. Виконано ретроспективний аналіз основних напрямків досліджень, проведених працівниками кафедри за весь період її функціонування. Розглянуто основні аспекти навчально-методичної роботи кафедри. Проаналізовано сучасний стан науково-дослідницької та навчально-методичної роботи, що виконується співробітниками кафедри, та представлено найбільш перспективні напрямки її подальшого розвитку.

The article is dedicated to the 90th anniversary of the Department of Electric Power Transmission of the National Technical University sKharkiv Polytechnic Institutes. The main stages of creation and development of the departmentare presented, data on outstanding specialists and scientists who took part in the creation and development of the department aregiven. A retrospective analysis of the main areas of research conducted by employees of the department for the entire period of its work. The main aspects of educational and methodical work of the department areconsidered. The current state of scientific and pedagogical work performed by the staff of the department is analysed, and the most promising areas ofits development are presented.
To the 90th anniversary of the department of electric power transmission of the National technical university "Kharkiv polytechnic institute"
Keywords: історична довідка; навчально-методична робота; науково-дослідна робота; historical reference; educational and methodical work; research work